The challenges for higher education to meet the demands of professionals in the sub-region of eastern Antioquia, Colombia - Vega-Monsalve, Ninfa del Carmen; Ruiz-Restrepo, Adriana María (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The challenges for higher education to meet the demands of professionals in the sub-region of eastern Antioquia, Colombia. The aim of this research was to establish training requirements at higher education level in the sub-region of eastern Antioquia, Colombia. The research entailed a review of existing literature, which was then contrasted with qualitative studies of businesses operating in productive sectors such as information and communication technologies (ICT), agro-industrial sectors and airports, ports and air terminals. The research showed that although most higher education programs were adequate, they failed to meet the emerging labour demands required by the productive sectors in the region. The key challenge for new study programs is the use of ICT for improving business productivity. In this sense, training programs should therefore embody a transdisciplinary approach that helps to improve production processes, enable the design of tailor-made programs, reduce production times, and facilitate process optimization and automation.